Two new species and new records of chigger mites (Acariformes: Trombiculidae) from South Africa. Issue 7 (3rd October 2022) - Stekolnikov, Alexandr A.; Matthee, Sonja
ABSTRACT: Based on a series of collections, two new species are described from South Africa, Kayella bothmai sp. n . and Schoutedenichia finisafricae sp. n ., parasitizing Micaelamys namaquensis (A. Smith) in Eastern and Northern Cape Provinces, respectively. The new species of Kayella Vercammen-Grandjean, 1960, recently recorded as Kayella sp., is the first species of this genus on the African continent. The species Schoutedenichia major Vercammen-Grandjean, 1958, which was described from the Democratic Republic of the Congo, is for the first time recorded in South Africa and on two species of murid rodents. Full morphometric and meristic data of Microtrombicula squirreli Stekolnikov, 2018 and Schoutedenichia paraxeri Vercammen-Grandjean, 1958, which were recently recorded in South Africa for the first time, are provided. http://urn:lsid:zoobank.org:pub:F9598A50-9E93-4DF3-B6F1-EB0FDDE6388D